Theodor Storm's Craft of Fiction The Torment of a Narrator - Bernd, Clifford A. (UNC Studies in the Germanic Languages and Literatures, 1966)
Bernd's study shows how Storm's "Novellen" are made purposeful by the operations of a fictional intelligence, haunted by the fear of passing time. The author challenges the traditional belief that Storm's narratives are products of a sentimental mind. No other discussion of Storm's tales, be it analysis of an individual narrative or collective treatment of several or all of them, seeks to interpret them with such specific emphasis upon their fictional, omniscient narrator. This concentration on the fictional narrator also leads into a study of Storm's subjective narrative form.